Interspeech 2018 2018
DOI: 10.21437/interspeech.2018-2446
|View full text |Cite
|
Sign up to set email alerts
|

Coherence Models for Dialogue

Abstract: Coherence across multiple turns is a major challenge for stateof-the-art dialogue models. Arguably the most successful approach to automatically learning text coherence is the entity grid, which relies on modelling patterns of distribution of entities across multiple sentences of a text. Originally applied to the evaluation of automatic summaries and the news genre, among its many extensions, this model has also been successfully used to assess dialogue coherence. Nevertheless, both the original grid and its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…EntityGrid and its extensions (Burstein et al, 2010;Guinaudeau and Strube, 2013;Mesgar and Strube, 2014;Tien Nguyen and Joty, 2017;Farag and Yannakoudakis, 2019) rely on entity transitions, as proxies of semantic connectivity, between utterances. These approaches are agnostic to discourse properties of dialogues (Purandare and Litman, 2008;Gandhe and Traum, 2008;Cervone et al, 2018 Inspired by EntityGrid, Gandhe and Traum (2016) define transition patterns among DA labels associated with utterances to measure coherence. Cervone et al (2018) combine the above ideas by augmenting entity grids with utterance DA labels.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…EntityGrid and its extensions (Burstein et al, 2010;Guinaudeau and Strube, 2013;Mesgar and Strube, 2014;Tien Nguyen and Joty, 2017;Farag and Yannakoudakis, 2019) rely on entity transitions, as proxies of semantic connectivity, between utterances. These approaches are agnostic to discourse properties of dialogues (Purandare and Litman, 2008;Gandhe and Traum, 2008;Cervone et al, 2018 Inspired by EntityGrid, Gandhe and Traum (2016) define transition patterns among DA labels associated with utterances to measure coherence. Cervone et al (2018) combine the above ideas by augmenting entity grids with utterance DA labels.…”
Section: Related Workmentioning
confidence: 99%
“…dialogue from a random sequence of dialogue utterances (Halliday and Hasan, 1976;Grosz and Sidner, 1986;Byron and Stent, 1998). Dialogue coherence deals with semantic relations between utterances considering their dialogue acts (Perrault and Allen, 1978;Cervone et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Entity Grid: Cervone et al (2018); Barzilay and Lapata (2008) show that entities and DA transitions across turns can be strong features for assessing dialog coherence. Starting from a grid representation of the turns of the conversation as a matrix (DAs × entities), these features are designed to capture the patterns of topic and intent shift distribution of a dialog.…”
Section: Featuresmentioning
confidence: 99%
“…Then it predicts the most likely DA of the next response based on the outputs of RNNs. Cervone et al (2018) showed that a DA is useful to improve the coherency of response. The predicted DAs can be used to generate a future response, which adds controllability and interpretability into a neural di-alogue system.…”
Section: Introductionmentioning
confidence: 99%